Why Banks in Emerging Markets Are Increasingly Providing Non-financial Services to Small and Medium Enterprises - International Finance Corporation (Washington, DC, 2017)
Banks in emerging markets are increasingly providing non-financial services to their SME clients, typically consisting of information sharing, training and consultancy. This study, published by IFC in partnership with the Austrian Government, is the first to explore reasons behind this trend, finding that banks' key motivations include attracting and retaining customers, and strengthening portfolio quality. The report consists of an overview followed by case studies of three banks, namely Türk Ekonomi Bankasý (TEB), Standard Chartered Bank (SCB), and ICICI Bank. It is estimated that there are 365 to 445 million formal and informal micro, small, and medium enterprises, with a subset of 25 to 35 million formal SMEs, in the developing world. Of these, 70 percent do not use external financing from financial institutions, although they are in need of it. Approximately 85 percent suffer from credit constraints.